Performa Perangkat Diagnostik Elisa Toksoplasmosis pada Serum Domba dan Manusia - Subekti, Didik T.; Hayati, Lisda; Raharja, Sujud M. (JURNAL BIOLOGI INDONESIA, 2012)
Performance of ELISA Toxoplasmosis Diagnostic Kits on Sheep and Human Sera Toxoplasma seropositivity in Indonesia have a high prevalence, both in human and animals. Unfortunately, the availability of diagnostic tools to support dynamic surveillance are limited. Recently, the diagnostic tools for toxoplasmosis, namely ELISA BM were developed. The technology was based on ELISA technique using soluble tachyzoite antigen from tachyzoites of Toxoplasma gondii. Kit performance is one of the important issue for acceptance of diagnostic tools prior to wide application. The purpose of the studies was to asses the quality of diagnostic toolsperformances. The assesment comprises of four stages. First stage was to evaluate the performance of ELISA BM compared to Latex Agglutination Test (LAT) on sheep sera. Secondly, to evaluate the performance of ELISA BM to descriminate true seropositive andseronegative toxoplasmosis on human sera. The last stage were comparing ELISA BM, ELISA TL (commercial kit) and LAT on predetermined and unknown human sera. The results showthat the accuracy of ELISA BM is slightly better than ELISA TL. Agreement of ELISA BM with LAT was better againts ELISA TL with LAT. However, all performance as determined using Cohenâs ? and Gwetâs AC1 of ELISA BM, ELISA TL and LAT were good up to very good agreement.Keywords: Toxoplasmosis, ELISA, Latex Agglutination, inter reliability agreement.